Brick as a Construction Material in the Modernization Process of The Ottoman Architecture - Ciftci, Aynur; Yergun, Uzay (TRANS TECH PUBLICATIONS LTD, 2010)
Brick used with stone in an alternate order -especially on monumental masonry buildings-is one of the basic construction materials in Ottoman classical architecture. Parallel to the announcement of Tanzimat Declaration (1839), to the political and economical relations improved with European states and to the industrial Revolution in Europe, an effective change had been seen on design concept and construction techniques in Ottoman architecture. Many new buildings were built using modern materials and imported techniques such as solid brick (in western norms) masonry walls, steel beams at the horizontal and vertical bearers, cement and concrete. The product of modern solid bricks in western standards had been realized in Ottoman territories in the last quarter of 19(th) century. The base of this research is constituted on 334 imported and local product solid bricks which remain to Zihni Goger's (firstly documented for this research), to Uzay Yergtin's, to Aynur Ciftci's and to the Yildiz Techical University, Department of Architectural Conservation's private collections. Most of the bricks are in a good condition, clean and have stamps. From the stamps one learns where they were produced, in which country or even city, the names of the plants, the logos and the dates of product. During the documentation every brick is numerated, photographed and a catalogue is prepared including the dimensions of the bricks. The demolotion of the buildings made of solid brick masonry walls-especially those which are not registered as an essential cultural asset- the interventions undertaken and the use of new materials during restoration of bearer walls have damaged the original bricks. Finally they were not conserved and documented. The aim of this paper is to determine the change of the production and the standarts of the bricks, to indicate their varieties, their fields of use and their conservation problems before and after the modernisation period of Ottoman architecture. It is intended to take into consideration the conservation and documentation of this material during renovations reflecting the original construction technique of the period that belongs to monumental and civil architecture.
Keywords: brick; Ottoman; architecture; modernization; imported; factorial; traditional; local; catalogue; collection; inscription; sign; stamp; Construction & Building Technology; Engineering; Materials Science